Assessing feasibility of routine identification tools for mental health disorder in neurology clinics. Issue 12 (11th May 2019) - Bennett, Sophie D; Heyman, Isobel; Coughtrey, Anna E; Buszewicz, Marta; Byford, Sarah; Dore, Caroline J; Fonagy, Peter; Ford, Tamsin; Moss-Morris, Rona; Stephenson, Terence; Varadkar, Sophia; Walker, Erin; et al.
Abstract : Objective: We aimed to test the feasibility of using an online parent-completed diagnostic assessment for detecting common mental health disorders in children attending neurology clinics. The assessment does not require intervention by a mental health professional or additional time in the clinic appointment. Setting: Two parallel and related screening studies were undertaken: Study 1: Tertiary paediatric neurology clinics. Study 2: Secondary and tertiary paediatric neurology clinics. Patients: Study 1: 406 Young people aged 7–18 attending paediatric neurology clinics. Study 2: 225 Young people aged 3–18 attending paediatric epilepsy clinics. Interventions: Parents completed online versions of the Strengths and Difficulties Questionnaire (SDQ) and Development and Well-being Assessment (DAWBA). Main outcome measures: We investigated: the willingness of families to complete the measures, proportion identified as having mental health disorders, time taken to complete the measures and acceptability to families and clinicians. Results: The mean total difficulties score of those that had completed the SDQ fell in the 'high' and 'very high' ranges. 60% and 70% of the DAWBAS completed met criteria for at least one DSM-IV disorder in study 1 and 2 respectively. 98% of the parents reported that the screening methods used were acceptable.